Modelling the pressure drop of two-phase flow through solid porous media. (March 2019) - Weise, Sonja; Meinicke, Sebastian; Wetzel, Thomas; Dietrich, Benjamin
Highlights: Pressure drop model for two-phase flow through porous media at high mass fluxes. Suggested model is based on homogeneous approach and Forchheimer equation. Prediction of Forchheimer coefficient is possible by different single-phase models. Model can predict 80% of all experimental data with a deviation of less than 30%. Abstract: This contribution discusses a physically meaningful model for the description of the pressure drop of two-phase flow through bi-continuous solid porous media like metal sponges (open-cell metal foams) at high mass fluxes (>25 kg m -2 s -1 ). Such conditions typically occur during flow boiling in tubes filled with solid sponges as a means to enhance heat transfer. We propose combining the homogeneous model for two-phase pressure drop in empty tubes and the Forchheimer equation describing the pressure drop of single-phase flow in porous media. For known geometrical characteristics of the sponge (i.e. the porosity, the specific surface area, and the window diameter), different prediction methodologies for the Forchheimer coefficient based on models developed for the single-phase pressure drop are compared. The validity range of the model is determined on the basis of all available literature data. If the geometric properties of the sponge are known, the model can predict 80% of all experimental data with a deviation of less than 30%. For experimentally determined single-phase Forchheimer coefficients, 96% of all data are predicted within 30% uncertainty.